Utilisation of Mining Waste for Production of Ceramic Tiles - Piotr Izak; Jurij Delihowski; Joanna Mastalska-Popławska; Agata Stempkowska (Applied Sciences)
This study proposes the utilisation of mining wastes, TG3 clay (Turoszów mining gangue) and post-flotation sludge (KGHM-Gilów), stored at a distance of about 150 km from each other in the region of Lower Silesia, Poland. From these wastes, mixtures were prepared for the production of ceramic tiles. Depending on the mutual proportions of the wastes, it is possible to obtain sintered stoneware-type ceramics with a mechanical bending strength of about 40 MPa and porous faience-type ceramics with a strength above 15 MPa. It is shown that the significant utilisation of these wastes is possible. The ceramic tiles were classified according to the applicable PN-EN 14411:2016 standard.